Interactive oral assessment in initial teacher education: Insights from pre-service teachers in Brunei - Desmond Chia Chun Tan (Universitas Syiah Kuala, 2026)
This study explores pre-service teachers’ (PST) perceptions and reflections of a formative Interactive Oral Assessment (IOA). Conventional assessment methods frequently fail to properly engage PSTs and tackle the emerging issue of academic dishonesty in the age of AI-assisted work. Driven by the need to promote academic integrity and workplace readiness, IOA is increasingly used as an alternative assessment approach in higher education institutions. This study reports the findings from a pilot study of 59 PSTs aimed at gathering their perceptions and reflections of their formative IOA experience in preparation for the summative IOA. The main data collection method was an online survey. The findings revealed that the majority of PSTs found IOA to be highly engaging and relevant in promoting critical reflection on their action research project in developing professional communication skills for different audiences. Scaffolded activities and formative feedback were essential supports that helped reduce anxiety and improve PSTs’ readiness for the summative IOA. Some PSTs expressed concerns regarding the rigidity and alignment of the IOA with actual workplace scenarios. The study concludes that IOA can serve as a promising complementary assessment tool for action research projects. The study contributes to emerging IOA literature by offering insights into how formative IOA can promote academic integrity and develop PSTs’ professional competencies, with implications for enhancing authenticity and integrity in higher-education assessments and informing innovative practices in teacher preparation.